2020
DOI: 10.1021/acsbiomaterials.0c00612
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Electrical Conductive and Phosphate Releasing Gel with Two-Dimensional Black Phosphorus and Carbon Nanotubes for Bone Tissue Engineering

Abstract: Injectable hydrogels have unique advantages for the repair of irregular tissue defects. In this study, we report a novel injectable carbon nanotube (CNT) and black phosphorus (BP) gel with enhanced mechanical strength, electrical conductivity, and continuous phosphate ion release for tissue engineering. The gel utilized biodegradable oligo­(poly­(ethylene glycol) fumarate) (OPF) polymer as the cross-linking matrix, with the addition of cross-linkable CNT-poly­(ethylene glycol)-acrylate (CNTpega) to grant mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 69 publications
0
56
0
Order By: Relevance
“…[169] To mimic the physiological microenvironment of bone, Liu et al reported injectable CNTs and black phosphorus (BP)-containing DCH with enhanced mechanical strength, electrical conductivity, and continuous phosphate ion release for tissue engineering. [170] The DCH utilized a biodegradable oligo-(poly-(ethylene glycol) fumarate) (OPF) polymer as the crosslinking matrix, with the addition of cross-linkable CNT-poly(ethylene glycol)-acrylate (CNTpega) to grant network formation and electroconductivity. BP nanosheets were incorporated to aid bone regeneration through the steady release of phosphate (through the environmental oxidation of phosphorus in situ).…”
Section: Dch-based Implantable Hydrogel Bioelectronicsmentioning
confidence: 99%
“…[169] To mimic the physiological microenvironment of bone, Liu et al reported injectable CNTs and black phosphorus (BP)-containing DCH with enhanced mechanical strength, electrical conductivity, and continuous phosphate ion release for tissue engineering. [170] The DCH utilized a biodegradable oligo-(poly-(ethylene glycol) fumarate) (OPF) polymer as the crosslinking matrix, with the addition of cross-linkable CNT-poly(ethylene glycol)-acrylate (CNTpega) to grant network formation and electroconductivity. BP nanosheets were incorporated to aid bone regeneration through the steady release of phosphate (through the environmental oxidation of phosphorus in situ).…”
Section: Dch-based Implantable Hydrogel Bioelectronicsmentioning
confidence: 99%
“…Synchronously, the MC3T3-E1 could continue to release vancomycin for 28 days, a promising material for osteomyelitis and bone regeneration. Also, scientists have recently synthesized new injectable CNT and black phosphorus (BP) gels, seen in Figure 4 [4]. e gels employed biodegradable oligo(poly(ethylene glycol) fumarate) (OPF) polymer as the crosslinked substrate, with the addition of a cross-linked CNTpoly(ethylene glycol)-acrylate (CNTpega) to provide mechanical support and electrical conductivity.…”
Section: Scaffold For Tissuementioning
confidence: 99%
“…e natural polymers cover fibrin, hyaluronic acid, chitosan, gellan, gelatin, collagen, alginate, and others. In contrast, the synthetic polymers include polylactide (PLA), poly(ethylene glycol) (PEG), poly(vinyl alcohol) (PVA), poly(2-hydroxyethyl methacrylate) (PHEMA), poly(lactic-co-glycolic acetic acid) (PLGA), polycaprolactone (PCL), poly(glycerol sebacate), and polyurethane (PU) [2][3][4][5][6]. Most of these polymers are nonconductive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations